DIGITAL RELIGION AND SHIFTING RELIGIOUS AUTHORITY: UNDERSTANDING PEOPLE'S BEHAVIOUR IN ACCESSING ISLAMIC WEBSITES - Shofa, Mila Faila; Ainun Yudhistira; Syafawi Ahmad Qadzafi (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2025)
Islamic websites are one form of new media that has attracted the attention of the Muslim community in Indonesia in the last few decades. Islamic websites contain Islamic beliefs, values, and traditions that are needed by people in the digital era. Therefore, this study aims to measure and map internet access behavior, especially access to Islamic websites in the Jabodetabek area and Surabaya City. This study uses a quantitative approach, collecting data through face-to-face interviews with 401 respondents. The results of this study indicate that regarding internet usage behavior, 40.2% of respondents fall into the Addicted User category, and 59.6% fall into the Medium User and Heavy User categories. The Islamic News Site is considered the most influential, trusted, and complete Islamic news media. Then, the National Islamic News, Islamic Trends, and Prayer columns are the three most commonly accessed columns by respondents on almost all Islamic websites.